2018
DOI: 10.4103/ejd.ejd_324_17
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of 2.5% sodium hypochlorite, 2% chlorhexidine, and ozonated water as irrigants in mesiobuccal root canals with severe curvature of mandibular molars

Abstract: Objective:The aim of this study is to evaluate the antimicrobial efficacy of 2.5% sodium hypochlorite, 2% chlorhexidine, and ozonated water on biofilms of Enterococcus faecalis, Streptococcus mutans, and Candida albicans in mesiobuccal root canals with severe curvature of mandibular molars.Materials and Methods:This was an experimental ex vivo study in microbiologic laboratory. Sixty mesiobuccal root canals with severe curvature of mandibular molars were contaminated with standard strains of E. faecalis, S. mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
(36 reference statements)
0
26
0
9
Order By: Relevance
“…Many different irrigation protocols have been used in endodontics to optimize the disinfection of the root canal. 7 8 9 10 Irrigation with activation using ultrasonic tips is a much-cited technique in the current literature. Passive ultrasonic irrigation (PUI) with the Irrisonic E1 tip (Helse; Santa Rosa do Viterbo, São Paulo, Brasil) was tested in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Many different irrigation protocols have been used in endodontics to optimize the disinfection of the root canal. 7 8 9 10 Irrigation with activation using ultrasonic tips is a much-cited technique in the current literature. Passive ultrasonic irrigation (PUI) with the Irrisonic E1 tip (Helse; Santa Rosa do Viterbo, São Paulo, Brasil) was tested in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Oral microbial communities are some of the most complex microbial floras in the human body, consisting of thousands of bacterial and hundreds of fungal species [25]. Culture-independent molecular methods, such as proteomics and 16S rRNA sequencing, have demonstrated that S. mutans was the dominant species, with elevated levels of other streptococci including Streptococcus sanguinis, Streptococcus mitis, and Streptococcus salivarius.…”
Section: Compounds With Activity Against Oral Infectionsmentioning
confidence: 99%
“…Also, chlorhexidine gluconate with tyrosol was revealed to be effective against single and mixed-species oral biofilms [57,58]. A solution containing 2.5% sodium hypochlorite, 2% chlorhexidine, and ozonated water inhibited biofilms of S. mutans and C. albicans in mesiobuccal root canals after irrigation [25]. A chlorhexidine carrier nanosystem based on iron oxide magnetic nanoparticles and chitosan was synthesized, and its antimicrobial effect on mono-and dual-species biofilms of C. albicans and S. mutans was evaluated.…”
Section: Chemical Compounds With Activity Against Streptococcus Mutanmentioning
confidence: 99%
“…The working length was set to the level of 1.0 as indicated on an electronic apex locator (Root ZX, J. Morita Manufacturing) by using K-files (Dentsply Maillefer, Ballaigues, Switzerland); the root canal was then enlarged up to a #20 file. Root canals were irrigated with 0.5 ml each time, in total 2 ml of 2.5% NaOCl (Neo Dental Chemical Products, Tokyo, Japan) [30]. The canals were dried with sterilized paper points (VDW, Munich, Germany) and filled with #20 gutta-percha points (SybronEndo, Orange, CA, USA) and root canal sealer (RealSeal SE, SybronEndo) according to the single-cone obturation technique [31].…”
Section: Root Canal Treatment In Ratsmentioning
confidence: 99%